The roles of light and pericarp on seed dormancy and germination in feral Raphanus sativus (Brassicaceae) - Vercellino, Roman Boris; Pandolfo, Claudio Ezequiel; Cerrotta, Alfonso; Cantamutto, Miguel Angel; Presotto, Alejandro Daniel (Wiley, 2019)
The timing of seed germination may determine the success of a weed species in an agroecosystem, and its expression is modulated by environmental conditions, but also by seed physiology and anatomy. The aims of this study were to investigate the roles of light, pericarp, dry storage and cold stratification on seed dormancy and germination in feral radish, a troublesome agricultural weed in temperate zones of the Americas that reduces crop yields. To this end, we used isolated intact pods and extracted seeds to test germination over time under contrasting temperature, light and storage conditions. Here, we showed that fresh seeds were non‐dormant, but that light and the presence of the pericarp reduced germination, especially under low temperatures. The pericarp reduced the final water content absorbed by seeds inside pods and decreased absorption/dehydration rates. The pericarp showed several small lignified cell layers in the endocarp, and x‐ray images displayed the lack of space between the partially embedded seed and the endocarp. Dry storage and cold stratification were ineffective in breaking the dormancy imposed by the pericarp. The apparent requirement for darkness and the mechanical restriction of the pericarp may have the potential to induce dormancy, spreading the timing of seed germination over a more extended period and hindering the control of feral radish.